Application of Characterized Source Model and Equivalent Hypocentral Distance for Probabilistic Seismic Hazard Assessment of the Nankai Trough Earthquakes - Jiao, Yuyu; Nojima, Nobuoto (Journal of disaster research, 2025)
This study aims to incorporate the effects of the spatial extent of the fault plane and the heterogeneous slip distributions in the probabilistic seismic hazard assessment (PSHA) of the Nankai Trough earthquakes. A method has been proposed to apply the characterized earthquake fault model (CEFM) developed for the probabilistic tsunami hazard assessment (PTHA) and the ground motion prediction equation employing the equivalent hypocentral distance (EHD) instead of conventional shortest fault distance (SFD). First, the PGV distributions were compared using the SFD and EHD with three different definitions of the weighting coefficients represented by the exponent (0, 1, and 2) of the slip amount. The results employing the EHD reflected the effect of the heterogeneous slip distributions, and the contrast became prominent with greater value of the exponent. Thereafter, in accordance with the scaling law of the fault parameters, the exponent was determined as 1 so that the contribution ratios of the large slip areas and the asperities in the characterized seismic source model are balanced in terms of seismic energy radiation. Analytical conditions for seismic and tsunami multi-hazard and risk assessment can be made consistent by employing the CEFM for both PSHA and PTHA.